Novel window thermoelectric module integration systems for building applications - Xu, Qi (2021)
The work covered in this thesis is an investigation of novel thermoelectric (TE) heat pump systems coupled with energy-efficient technologies (heat recovery ventilation and evaporative cooling) for small single room applications. In the first part of the thesis, a window thermoelectric based heat pipe heat recovery ventilator (WTEHPV) unit for heating purpose was designed and evaluated by experimental investigation and theoretical modelling. Both the experimental investigations on the prototypes without and with air filter assembled were carried out within an environmental control chamber under laboratory condition. The results showed that with the working current for thermoelectric modules increasing, the heating generation rate will increase, while the Coefficient of Performance for heating purposes (COPh) shows a decreased trend. During the whole testing, the maximum temperature rise of 7.9 °C and the maximum heating capacity of 172W were obtained for the WTEHPV system at the operating current of 3A for TE modules. The COPh of the prototype ranged from 1.71 to 1.34 with operating current ranged from 1A to 3A. By comparison of the experimental results and modelling results, the modelling showed an acceptable agreement with the testing, that could be developed for further performance evaluations.